AB0001 Still's Disease – Similar Gene Expression Profiles Demonstrate Presence of an IL-1 Response Signature in SJIA and AOSD. (9th June 2015) - Brachat, A.; Feist, E.; Behrens, F.; Blank, N.; Nanguneri, N.; Specker, C.; Witt, M.; Zernicke, J.; Martini, A.; Junge, G.
Abstract : Background: Adult-onset Still's disease (AOSD) is a rare auto-inflammatory disorder resembling a similar pediatric syndrome known as systemic juvenile idiopathic arthritis (SJIA). 1 The superimposable systemic and clinical features in SJIA and AOSD suggest that both clinical phenotypes represent a disease continuum with a pediatric (SJIA) and more adult-onset (AOSD). The authors believe that the analyses of gene expression profiles can be useful not only for disease classification, diagnosis, and prognosis, but also to identify disease specific treatment effects that counteract the underlying pathological mechanisms. In the analysis described here, we address the question: How do genes that respond to canakinumab treatment in SJIA patients 2 behave in AOSD patients with active disease relative to healthy controls and prior to IL-1 targeting therapy? Objectives: To determine how genes that respond to IL-1β blockade with canakinumab in SJIA patients behave in AOSD patients relative to healthy controls. Methods: SJIA gene expression profiles pre- and post canakinumab treatment were compared with AOSD patients relative to healthy subjects using Affymetrix U133Plus 2 DNA microarrays. Expression values of genes are shown for healthy subjects and AOSD patients prior to canakinumab treatment (genes are shown in rows and patient samples in columns). Results: Consistently, all genes down-regulated in SJIA following canakinumab treatment were upregulated in a majority of AOSD patients with active disease relative to healthy subjects and prior to canakinumab treatment. A few of the AOSD patients resembled healthy subjects (Figure ). Comparison of the gene expression patterns to neutrophil counts suggested that elevated neutrophil numbers were closely correlated to the up-regulation of IL-1 associated gene expression. Conclusions: Results are consistent with and further support the concept of a Still's disease continuum that presents as pediatric/juvenile SJIA or adult-onset Still's disease. Moreover, they suggest that AOSD is an IL-1 driven condition that is also mechanistically similar to SJIA and that the observed canakinumab response signature is likely to show a comparable treatment response to IL-1β blockade in AOSD. References: Martini A. Ann Rheum Dis 2012; 71(9):1437-39. Brachat A, et al. Ann Rheum Dis 2014;73(Suppl2): 62. Disclosure of Interest: A. Brachat Employee of: Novartis, E. Feist Grant/research support from: Novartis, Consultant for: Novartis, Speakers bureau: Novartis, F. Behrens Grant/research support from: Pfizer, Roche, Abbvie, Chugai, Consultant for: Abbvie, Pfizer, Celgene, Novartis, Chugai, Astra Zeneca, Lilly, Janssen, Merck, Morphosys, Speakers bureau: Abbvie, Pfizer, Celgene, Novartis, Chugai, UCB, Astra-Zeneca, Janssen, Roche, Lilly, N. Blank Grant/research support from: Novartis, SOBI, Amgen, BMS, Pfizer, Roche, Abbvie and others, Speakers bureau: Novartis, SOBI, Amgen, BMS, Pfizer, Roche, Abbvie and others, N. Nanguneri Employee of: Novartis, C. Specker: None declared, M. Witt: None declared, J. Zernicke: None declared, A. Martini Grant/research support from: Abbott, Bristol Myers and Squibb, Francesco Angelini S.P.A., Glaxo Smith & Kline, Janssen Biotech Inc Novartis, Pfizer Inc, Roche, Sanofi Aventis, Schwarz Biosciences GmbH: I declare that the GASLINI Hospital which is the public Hospital where I work as full time employee has received contributions to support the research activities of the network of PRINTO (www.printo.it ), Consultant for: Bristol Myers and Squibb, Centocor Research & Development, Glaxo Smith & Kline, Novartis, Pfizer Inc, Roche, Sanofi Aventis, Schwarz Biosciences GmbH, I declare that the Gaslini Hospital which is the public Hospital where I work as full time employee has received contributions to support the PRINTO research activities from the industries above mentioned., Speakers bureau: Abbott, Abbvie, Amgen, Biogenidecm Bristol MyersSquibb, Astellas, Behringer, Italfarmaco, Janssen, MedImmune, Novartis, NovoNordisk, Pfizer, Sanofi, Roche, Servier., G. Junge Employee of: Novartis